METHODICAL ANALYSIS OF TEXTBOOKS AND IMPROVEMENT OF EDUCATIONAL TASKS IN THE CONTENT OF MOTHER TONGUE EDUCATION - Gulbahor Rasulova (The Bioscan, 2024)
The current state and prospects for the transition to a credit-modular system for the development of oral competence of students of higher philological education, the principles of a credit-modular system of universities based on advanced foreign experience, recognition of learning outcomes. Substantiated are academic mobility, the accumulation of grades, the interest of teachers and students in science, as well as the introduction of a well-defined assessment system.